Rapid adaptive adjustment of parental care coincident with altered migratory behaviour - Jonker, Rudy M.; Kurvers, R. H. J. M.; van de Bilt, A.; Faber, M.; Van Wieren, S. E.; Prins, H. H. T.; Ydenberg, R. C. (Evolutionary ecology, 2012)
The optimal duration of parental care is shaped by the trade-off between investment in current and expected future reproductive success. A change in migratory behaviour is expected to affect the optimal duration of parental care, because migration and non-migration differ in expectations of future reproductive success as a result of differential adult and/or offspring mortality. Here we studied how a recent emergence of non-migratory behaviour has affected the duration of parental care in the previously (until the 1980s) strictly migratory Russian breeding population of the barnacle geese Branta leucopsis . As a measure of parental care, we compared the vigilance behaviour of parents and non-parents in both migratory and non-migratory barnacle geese throughout the season. We estimated the duration of parental care at 233 days for migratory and 183 days for non-migratory barnacle geese. This constitutes a shortening of the duration of parental care of 21% in 25 years. Barnacle geese are thus able to rapidly adapt their parental care behaviour to ecological conditions associated with altered migratory behaviour. Our study demonstrates that a termination of migratory behaviour resulted in a drastic reduction in parental care and highlights the importance of studying the ecological and behavioural consequences of changes in migratory behaviour and the consequences of these changes for life-history evolution.